Augmentation of Lysosomal Phospholipase A2 Activity in the Anterior Chamber in Glaucoma. (3rd May 2016) - Hiraoka, Miki; Abe, Akira; Inatomi, Shuichiro; Sawada, Kanako; Ohguro, Hiroshi
Abstract: Aim : The lysosomal enzyme in the anterior chamber has a crucial role in the digestion of the insoluble materials in the aqueous humor (AH). The dysfunction of AH filtration in the trabecular meshwork (TM) causes increasing AH outflow resistance in the TM. Those insoluble objects, including phospholipids, should be digested in the TM for normal outflow. The present study was conducted to explore the involvement of lysosomal phospholipase A2 (LPLA2), a phospholipid-degrading enzyme, of the AH in glaucoma using clinical AH specimens. Materials and Methods : One hundred and twenty-five AH specimens were collected from patients. The measurement of LPLA2 activity in the AH was carried out using liposomes consisting of phosphatidylglycerol and N -acetylsphingosine (NAS). The correlation between the LPLA2 activity in the AH and ocular diseases was investigated. Results : The human AH showed both transacylation of NAS and the release of fatty acids under acidic conditions but not at a neutral pH, which is consistent with the known properties of LPLA2. The LPLA2 activity in the AH was not affected by age or systemic disease. A comparison between ocular diseases showed that the AH specimens obtained from patients with glaucoma had significantly higher LPLA2 activity than the other ocular disease groups. Discussion : The present findings suggest that the ascended level of LPLA2 activity in the AH of glaucoma patients is associated with the development of glaucoma.